2010
DOI: 10.4049/jimmunol.0902999
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft Th17 Infiltrate Promotes Lymphoid Neogenesis and Hastens Clinical Chronic Rejection

Abstract: To evaluate the influence of intragraft inflammatory infiltrate on the course of chronic rejection, 11 human renal grafts, detransplanted for terminal failure, were analyzed. Samples were divided into two groups according to their graft survival (> or ≤8 y). In both groups, the main cell population infiltrating the graft interstitia was T lymphocytes. The extent of the lymphocytic infiltration and the distribution of naive and memory, CD4+ and CD8+ T cells, were similar in both groups. Although all type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
130
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 46 publications
10
130
0
Order By: Relevance
“…In cardiac and lung transplantation models, IL-17 deficiency is associated with high numbers of regulatory cells and prolonged graft survival (26) and activation of the Th17 pathway strongly promotes chronic rejection (27). In kidney transplantation, Th17 cells within the explanted kidney allograft are associated with rapidly progressing chronic rejection (28). The effect of this Th17-mediated response during acute rejection in recipients of a marginal kidney will require follow-up biopsies after the initial TCMR episode.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac and lung transplantation models, IL-17 deficiency is associated with high numbers of regulatory cells and prolonged graft survival (26) and activation of the Th17 pathway strongly promotes chronic rejection (27). In kidney transplantation, Th17 cells within the explanted kidney allograft are associated with rapidly progressing chronic rejection (28). The effect of this Th17-mediated response during acute rejection in recipients of a marginal kidney will require follow-up biopsies after the initial TCMR episode.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL-17A-expressing CD4 + T cells, more than IFN-g-producing CD4 + Th1 cells, play an important role in rejection and vasculopathy in clinical solid organ transplantation [21][22][23]. Twelve-month transplant specimens from CsA-treated patients showed important mononuclear cell infiltrates in which IL-17A-producing CD4 + T cells were clearly evident, even in the absence of acute rejection criteria; this process was accompanied by fibrosis and hyaline material.…”
Section: Discussionmentioning
confidence: 99%
“…Through control of lymphoid chemokine production in epithelial and fibroblastic stromal cells, IL‐22 also drives lymphoid neogenesis in mice following salivary gland cannulation with adenovirus 23. Podoplanin and IL‐17 have also been linked with ectopic lymphoneogenesis in human diseases 21, 24, 25…”
Section: Cellular Initiators Of Ectopic Lymphoneogenesismentioning
confidence: 99%